"Auditoria operativa y su relación con los servicios del área de crédito del banco nacional de fomento, sucursal La Mana, periodo 2012." - Murillo Cepeda, Manuel Antonio (2015)
This research project aims to conduct an operational audit services in the area of credit from the National Development Bank Branch The Maná period 2012 to discuss administrative policies and regulations, evaluate internal control that the bank has applied measure the confidence level of the credit system, and report where an audit firm is created. The development of this process not used the experimental design and exploratory research and a descriptive model facilitated because I know in detail the operational characteristics of the institution. The research was developed through a thorough examination in the operational management, the COSO method 1 was applied to their respective components, showing how internal control results in the area of credit risk control 20,40%, the inherent risk of 19,00% and the risk of audit 0,04%, so if the credit department is developing its activities in credit concessions can be seen that the lines are more catered for agricultural and livestock consume. For the findings it is recommended that the credit institution continues to operate while maintaining the policies demanded by the government body that lead to improve operational process and ensure proper operation thereof..